Plants Around Us - Dixon Malcolm (Evans Brothers Limited, 1998)
Plants Around Us introduces young readers to a wide range of plants,from trees and decorative flowers to fruits and vegetables. The activities allow young children to investigate roots, leaves, stems and flowers, to grow seeds andbulbs and to discover some of the ways in which we depend on plants in our everyday lives.
Keywords: Non-Fiction / Plants